Pengembangan Modul Mitigasi Bencana Alam Berbasis Science, Technology, Engineering, and Mathematic untuk Pembelajaran Peserta Didik Jenjang SMA - Zakiah Ulfa; Rajibussalim Rajibussalim*; Teuku Alvisyahrin (Universitas Syiah Kuala, 2020)
Knowledge of natural disasters is a science that everyone should have. This led the government to take policy by incorporating disaster mitigation materials into the school learning curriculum. Natural disaster mitigation modules based on science, technology, engineering and mathematics (STEM) are considered to support learning that can encourage students to be active, creative, innovative in doing group work and completing experimental projects that can solve real problems because it contains STEM-based worksheets to help students to understand the material more quickly. The purpose of this study was to determine the process of developing a STEM-based natural disaster mitigation learning module and the learning outcomes of class XI SMA / MA students in the city of Banda Aceh. The research method used in this research is research and development with a development model of analysis, design, development, implementation, and evaluation (ADDIE). In this study, several data collection was carried out starting with the needs analysis data, STEM based module validation data, response data, and student learning outcomes. The validation of module evaluation used Aiken's V test. T-test results for the experimental class showed a significant difference in the student learning outcomes of SMA/ MA in Banda Aceh after learning natural disaster mitigation using STEM-based modules.